Student’s Student’s Reception about La Parure, an Ironical Short Story by Guy de Maupassant - Zuleika, Tika (International Journal of Education, Information Technology, and Others, 2025)
This study explores students’ reception of La Parure, an ironic short story by Guy de Maupassant, focusing on how they interpret its themes, characters, and moral messages. Employing a reception theory framework, the research analyses responses from students with diverse cultural and academic backgrounds. Data were collected through questionnaires, interviews, and textual analysis to understand how readers perceive the story’s critique of social class, materialism, and the consequences of appearances. Findings reveal varying receptions based on cultural and temporal contexts. Students often empathize with the protagonist, Mathilde Loisel, while simultaneously critiquing her obsession with social status. The study also highlights the relevance of La Parure in modern contexts, particularly in addressing materialism and the pursuit of superficial appearances, akin to contemporary phenomena like social media lifestyles. Additionally, the analysis examines students’ perceptions of adaptations of La Parure into films and graphic novels, revealing how different media influence their understanding of the story's irony and moral lessons.